IMPROVING THE PROFESSIONALITY OF SCHOOL PRINCIPALS AND TEACHERS TOWARDS “SEKOLAH PENGGERAK” PROGRAMS IN DARUL FAQIH INDONESIA - Faris Khoirul Anam; Abd. Rauf Hassan; Ikhsan, M. Alifudin; Abdul Adzim; Zahrotul Muzdalifah (Wisesa: Jurnal Pengabdian Masyarakat, 2023)
The professionalism of school principals and teachers is an important part in advancing the institution. Several studies show that the level of success of schools in achieving their learning goals is influenced by how professional the resources they have are. Professionalism can be formed with an organized system. School quality is a serious concern for the government, which is manifested by changes to curriculum schemes and various superior programs such as the driving school program. This activity aims to provide education, assistance and initial assessment of the school's suitability as a driving school based on applicable regulations. This activity was carried out at Darul Faqih Indonesia Middle School, and was also attended by 30 state and private middle schools in Malang Regency. The method used in community service activities is divided into two phases, namely the training and empowerment phase and the assessment phase. The results of this activity show that the professional level of school principals and teachers is an indicator of the school's success in achieving the desired educational targets.